Management theory : a critical and reflexive reading - Monin, Nanette (London ; New York : Routledge, 2004)
The book has been constructed as the story of the author's own research journey, using a unique blend of management theory and poetry.
Includes bibliographical references (p. [214]-227) and index.
aug 28/05/13
Loans
Keywords: Management; Management theory